Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1074/jbc.m109.077800
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulation of Myocardial Triglyceride Metabolism by the Cardiomyocyte Circadian Clock

Abstract: Maintenance of circadian alignment between an organism and its environment is essential to ensure metabolic homeostasis. Synchrony is achieved by cell autonomous circadian clocks. Despite a growing appreciation of the integral relation between clocks and metabolism, little is known regarding the direct influence of a peripheral clock on cellular responses to fatty acids. To address this important issue, we utilized a genetic model of disrupted clock function specifically in cardiomyocytes in vivo (termed cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(179 citation statements)
references
References 37 publications
7
162
1
Order By: Relevance
“…Cellular mechanisms exist in the cardiovascular system, like in every eukaryote cell, that orchestrate oscillation of tissue function during a 24-hour period. For instance, experimental studies have shown that cardiac redox status and fatty acid metabolism, 6,15 but also myocardial contractile function, are regulated in a circadian manner. 16 It is therefore tempting to wonder whether ischemic stress would have a different impact on the myocardium over a 24-hour period.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular mechanisms exist in the cardiovascular system, like in every eukaryote cell, that orchestrate oscillation of tissue function during a 24-hour period. For instance, experimental studies have shown that cardiac redox status and fatty acid metabolism, 6,15 but also myocardial contractile function, are regulated in a circadian manner. 16 It is therefore tempting to wonder whether ischemic stress would have a different impact on the myocardium over a 24-hour period.…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in lipid absorption do not show circadian expression in Clock mt/mt mice and remain irresponsive to restricted feeding Pan et al, 2010). Clock mutant mice also display altered rhythmic expression of genes involved in TG synthesis and lipolysis (Kudo et al, 2007;Shostak et al, 2013;Tsai et al, 2010). Loss of BMAL1 in mice leads to a disruption of the daily oscillation of plasma TG (Rudic et al, 2004).…”
Section: Role Of Clock Components In Lipid Metabolismmentioning
confidence: 99%
“…For this reason we have recently utilized a mouse model wherein the circadian clock is genetically disrupted in a specific, metabolically active organ (namely the heart) (13,15). Cardiomyocyte-specific clock mutant (CCM) 4 mice have recently revealed that this cell autonomous clock regulates in a time-of-day-dependent manner 1) expression of a plethora of key genes known to influence both oxidative and non-oxidative metabolism, 2) responsiveness of the heart to fatty acids at transcriptional and metabolic levels, and 3) triglyceride turnover (13,15,16). Cardiomyocyte clock control of myocardial metabolism is associated with time-of-day-dependent alterations in both myocardial function (e.g.…”
mentioning
confidence: 99%